MOLECULAR GENETICS AND PATHOGENESIS OF CHRONIC MYELOPROLIFERATIVE NEOPLASMS: THE ROLES OF JAK2 V617F, CALR, MPL MUTATIONS, AND THE JAK-STAT PATHWAY - Jakhonov Azizbek Kholmirzaevich,; Jakhonov Azizbek Kholmirzaevich, (TADQIQOTLAR, 2025)
Abstract:  Chronic  Myeloproliferative  Neoplasms  (MPNs)  are  clonal disorders  of  hematopoietic  stem  cells  characterized  by  excessive  proliferation  of myeloid  lineages.  The  pathogenesis  of  these  disorders  is  closely  associated  with somatic mutations in genes that control intracellular signaling. Among these, mutations in JAK2 (V617F), CALR (Calreticulin), and MPL (myeloproliferative leukemia virus oncogene) are the most commonly implicated in BCR-ABL-negative MPNs. These mutations result in constitutive activation of the JAK-STAT pathway, leading to uncontrolled cell growth, survival, and cytokine hypersensitivity. Understanding these genetic  alterations  is  essential  for  accurate  diagnosis,  prognosis,  and  treatment  of MPNs. This article provides an in-depth review of the genetic mechanisms underlying MPNs,  focusing  on  the  roles  of  JAK2  V617F,  CALR,  MPL,  and  the  JAK-STAT signaling  pathway,  and  highlights  current  and  emerging  targeted  therapies  that  are shaping modern clinical practice.